Mood, neuromuscular function, and performance during training in female swimmers - Raglin, J. S.; Kocjea, D. M.; Stager, J. M.; Harms, C. A. (Medicine & Science in Sports & Exercise, 1996)
Twelve collegiate female swimmers were measured on various factors during pre-season, peak training, and taper. During peak training neuromuscular function (-8.6% -- motoneuron excitability) and peak anaerobic swimming power (-9.4% -- tethered swimming test) were reduced below baseline (pre-season) levels. Mood disturbance was also above baseline. These variables returned to baseline values during taper. Implication: These types of response are similar to those recorded for males. However, more importantly one has to question the value of suppressing anaerobic power and neuromuscular function during training to only have these capacities return to pre-season values. Since they are important factors in explosive performances one would expect they should be improved rather than repressed in adaptive training.